Study and Design of the Planetary Reducer Selection System - Zhou Rui; Dong Mingwang; Bao Kaimei (Jixie chuandong)
Aiming at the difficulties in the selection of planetary reducer in an enterprise,a planetary reducer selection software is developed to improve the efficiency of selection. The software is developed based on Visual Basic 6. 0 and Access 2013,the XML format is used for formula storage. By analyzing the selection process and the factors of the selection,the required parameters are selected,the calculation formula of motor-reducer-load transmission process is analyzed and deduced. The database,calculation module,auxiliary function module and planetary reducer selection system are designed. Finally,the feasibility of the planetary reducer selection system is verified by concrete examples.